2012
DOI: 10.1242/jcs.101675
|View full text |Cite
|
Sign up to set email alerts
|

SDF and GABA interact to regulate axophilic migration of GnRH neurons

Abstract: SummaryStromal derived growth factor (SDF-1) and gamma-aminobutyric acid (GABA) are two extracellular cues that regulate the rate of neuronal migration during development and may act synergistically. The molecular mechanisms of this interaction are still unclear. Gonadotropin releasing hormone-1 (GnRH) neurons are essential for vertebrate reproduction. During development, these neurons emerge from the nasal placode and migrate through the cribriform plate into the brain. Both SDF-1 and GABA have been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 80 publications
5
61
0
Order By: Relevance
“…Signaling via stromal cell-derived factor 1 (SDF-1) and its receptor CXCR4 is required for survival and migration of GnRH neurons during embryonic development [100,101]. It has been shown that simultaneous activation by GABA and SDF-1 acts synergistically to stabilize linear rather than random movement of migratory GnRH neurons [102]. Our data indicate that CXCR4 is also expressed in adult GnRH neurons at the mRNA level and exhibits male-specific upregulation.…”
Section: Discussionmentioning
confidence: 79%
“…Signaling via stromal cell-derived factor 1 (SDF-1) and its receptor CXCR4 is required for survival and migration of GnRH neurons during embryonic development [100,101]. It has been shown that simultaneous activation by GABA and SDF-1 acts synergistically to stabilize linear rather than random movement of migratory GnRH neurons [102]. Our data indicate that CXCR4 is also expressed in adult GnRH neurons at the mRNA level and exhibits male-specific upregulation.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, omission of the primary antibody (single stain) resulted in no detectable signal and omission of the second primary (double stain) resulted in no doublelabeled structures (data not shown). Pictures were taken as previously described (20,32,34). Fluorescent images were taken on a spinning disk confocal system CSU10 (Yokogawa) mounted on an Eclipse TE200 microscope (Nikon) using an EMCCD ImageM digital camera (Hamamatsu) with I-Vision software (Biovision).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Images were taken with an ELWD 20x objective (Nikon). Both linear distance and total distance were measured as previously described (20,34). Total distance reflects the entire route that the cell moved while linear distance equals the change between the first position and final position.…”
Section: Primary Nasal Explantsmentioning
confidence: 99%
See 2 more Smart Citations